STRUKTUR KOMUNITAS IKAN FAMILY CHAETODONTIDAE SEBAGAI INDIKATOR KONDISI KESEHATAN LINGKUNGAN EKOSISTEM TERUMBU KARANG DI ZONA TRADISIONAL PULAU BUNAKEN TAMAN NASIONAL BUNAKEN - Frengki Palendeng; Janny Dirk Kusen; Indri Selovita Manembu (Sam Ratulangi University, 2021)
The presence of coral reef fishes, especially family Chaetodontidae is one of bioindicators to environment health condition of coral reef. Fish indicator research in Bunaken Island waters aims to find out the community structure, such as the composition, abundance, density, equality, diversity and dominance. Data collection was conducted at 5 (five) locations in the Bunaken Island Traditional Zone where there are 5 (five) observation points respectively, namely TP-1 Mandolin, TP-2 Alung Banua, TP-3 Sachiko, TP-4 Muka Kampung, and TP-5 Bunaken Timur. Data collection by underwater visual census (UVC) techniques using SCUBA. The results showed there were 23 species of indicator fish from family Chaetodontidae, total individuals number of each species in 5 research sites as many as 97 individuals. The highest fish density is 0.06 at TP-5 while the lowest value in TP-2 with density value 0.02. Through indicator fish community structure indicates that the coral reef quality conditions is stable indicated by diversity values (H') in all locations were moderate category and inversely proportional by low dominance values, high leveling values (E). The similarity rate (IS) of indicator fish species in all locations differs from each other indicating the condition of coral reefs in each location grows independently without being influenced by other locations.Keywords: Reef Fish, Coral Reef, Indicator Fish.